Designing an Interactive and Educational Virtual Reality Game for Museum Bahari - Arief, Fadilah Husna; Wiradarmo, Aulia Ardista; Widharsyah, Redha; Palesangi, Muliadi (VCD, 2025)
This study explores the potential of Virtual Reality (VR) technology to enhance museum visitor engagement through the “Jelajah Bahari” VR game at Museum Bahari, DKI Jakarta. By integrating VR, the museum offers an immersive and interactive experience that brings Indonesia’s maritime heritage to life. This VR game combines educational content with an engaging narrative, allowing users to embody a Pinisi ship captain on a journey to Kepulauan Seribu. It was tested by museum staff and evaluated qualitatively. It showed positive responses to the game’s design and educational value, highlighting VR game’s potential to increase visitor’s curiosity and engage younger audience. However, challenges like VR unfamiliarity, equipment maintenance, and visitor safety considerations were noted as essential to successful implementation. These findings indicate that, with proper support, VR installations can significantly benefit Indonesian museums by making historical education more engaging and accessible. Overall, the “Jelajah Bahari” VR game serves as a model for other museums seeking to integrate immersive technology, showcasing VR’s potential to elevate traditional exhibits and broaden cultural engagement in an evolving digital landscape.